AC and DC stability analysis method considering receiving end excitation system - WANG YUNPENG; MA CHANGHUI; YANG JINHONG; LI WENBO; LI ZHI; WU NAIHU; YANG DONG; JIANG ZHE; LI MING; ZHANG XINYI; XING LUHUA; ZHANG DANDAN (2015)
The invention discloses an AC and DC stability analysis method considering a receiving end excitation system. The AC and DC stability analysis method comprises the steps of: determining a control mode and parameters of a DC power transmission system; carrying out expanded load flow calculation on an AC and DC system while considering excitation parameters of a generator and an amplitude limiting link of an excitation link thereof; and analyzing stability of the system according to load variation, receiving end Thevenin equivalent parameter variation and parameters of the DC power transmission system. The AC and DC stability analysis method considers the amplitude limiting link of the excitation system, and illustrates the supporting role of the excitation link of the generator to voltage through the combination of the traditional receiving end Thevenin equivalent parameters; and the supporting capacity of a receiving end system to DC drop-in is embodiment of the interaction of power grid structure, receiving end load and generator excitation.